Design of a method te detect alcoholic beverage tampering :SalusOI (2018)
"Currently, approximately 17 percent of all the alcohol consumed in Colombia is tampered with methanol. Although small doses of this substance do not have considerable negative effects on human health, in high doses, methanol poisoning may cause blindness, liver or kidney failure, and death. This is because of an ineffective and obsolete control system over the quality of alcoholic beverages and a lack of responsibility and culture around the consumption of alcohol that thousands of cases of methanol poisoning are reported each year. SalusOl provides a new solution capable of detecting the abnormal presence of methanol in alcoholic beverages in an effective, efficient, and accurate manner. Now, in addition to reducing the number of cases of methanol poisoning, this product's objective is to promote the responsible consumption of alcoholic beverages. To do so, an alcohol oxidase enzyme, obtained from the yeast Pichia pastoris, specific to methanol was used as a biosensor capable of selectively oxidizing methanol into hydrogen peroxide; a chemical compound capable of being detected as it changes the electrical properties of the sample and, has the ability to oxidize o-dianisidine changing its color."--Tomado del Formato de Documento de Grado